THE WONDER FOOD MUSEUM STORY: CELEBRATING MALAYSIA’S FOOD CULTURE AND CULINARY HERITAGE - SER, ShawHong (E-Journal of Cultural Studies; Volume 13, Number 4, November 2020DO - 10.24843/cs.2020.v13.i04.p04, 2020)
Although thematic museums centered around food culture and culinary heritage have been around for decades, the concept of food museum is still fairly new in Southeast Asia. Only in 2015, the first food-oriented museum – “Wonder Food Museum” was established in Penang, Malaysia. Since its establishment, the museum has received positive feedback from both local and international visitors. From 2017 to 2019, the museum has been selected as the recipient of the Certificate of Excellence by international well renowned Travel organization - TripAdvisor Inc. Meanwhile, the museum’s contribution to the state’s cultural and tourism development has also been recognized by the state authority. In 2017 and 2019, the museum was awarded the ‘Top Museum Award (Unique Concept)’, and ‘Best Tourism (Museum)Award’ by the INPenang International Awards respectively. By and large, Wonder Food Museum is currently one of the most outstanding museums in Malaysia and a wellknown attraction in Penang. In this paper, to response on the research scholarly interest in museum tourism in Southeast Asia, the researcher has made an attempt to document the development of Wonder Food Museum from 2015 to 2019. The museum’s curatorial concept, exhibits production, exhibition planning and its overall management will be discussed and analyzed. As the aforementioned this paper will provide insights into an understanding of food museum’s development in Malaysia. Keywords : Food museum, food culture, culinary heritage, Malaysia’s museum, museum tourism, interactive museum